2018
DOI: 10.1109/tifs.2017.2753172
|View full text |Cite
|
Sign up to set email alerts
|

Ranking-Based Locality Sensitive Hashing-Enabled Cancelable Biometrics: Index-of-Max Hashing

Abstract: Abstract-In this paper, we propose a ranking based locality sensitive hashing inspired two-factor cancelable biometrics, dubbed "Index-of-Max" (IoM) hashing for biometric template protection. With externally generated random parameters, IoM hashing transforms a real-valued biometric feature vector into discrete index (max ranked) hashed code. We demonstrate two realizations from IoM hashing notion, namely Gaussian Random Projection based and Uniformly Random Permutation based hashing schemes. The discrete indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(104 citation statements)
references
References 44 publications
0
103
0
1
Order By: Relevance
“…A total number of 4950 trials for imposter attempts and 2800 trials for genuine attempts were recorded. However, because different nonce is used, we named the genuine attempt (under same subject) as pseudo imposter attempt follows [19]. Figure 3 shows the pseudo imposter score and imposter score, which corresponds to the normalized genuine pairs count.…”
Section: Revocabilitymentioning
confidence: 99%
“…A total number of 4950 trials for imposter attempts and 2800 trials for genuine attempts were recorded. However, because different nonce is used, we named the genuine attempt (under same subject) as pseudo imposter attempt follows [19]. Figure 3 shows the pseudo imposter score and imposter score, which corresponds to the normalized genuine pairs count.…”
Section: Revocabilitymentioning
confidence: 99%
“…According to the international standard ISO/IEC 24745: biometric information protection, the biometric template protection schemes must meet these properties: irreversibility, unlinkability, revocability and performance [5]. The irreversibility means the reconstruction from the protected biometric template to the original image or the biometric sample, should be difficult.…”
Section: Biometric Template Protectionmentioning
confidence: 99%
“…A complete review of cancelable biometric systems can be found in [17]. Very recently, Teoh et al [10] proposed a new two-factor scheme to protect the biometric template by transformation. Compared with previous works, this method is based on localized random projection and on the rank correlation.…”
Section: Related Workmentioning
confidence: 99%
“…These particular biometric systems must of course address classical issues such as a high level of performance (i.e., minimizing the Equal Error Rate (EER) or Area Under the Curve (AUC) value of the system) but also new constraints concerning privacy. In the literature, many papers have been published dealing with the definition of new schemes for the protection of biometric templates (such as those presented in [2], [10], [21], [29]).…”
Section: Introductionmentioning
confidence: 99%